Кон Lorraine Code, Ecological Thinking: The Politics of Epistemic Location: Për Lorraine Code, Ecological Thinking: The Politics of Epistemic Location - Badarevski, Bobi; Ahmeti, Xhabir (Identities: Journal for Politics, Gender and Culture, 2007)
Author(s): Bobi Badarevski | Боби Бадаревски Title (Macedonian): Кон Lorraine Code, Ecological Thinking: The Politics of Epistemic Location Title (Albanian): Për Lorraine Code, Ecological Thinking: The Politics of Epistemic Location Translated by (Macedonian to Albanian): Xhabir Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 1 (Winter 2007) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 215-220 Page Count: 6 Citation (Macedonian): Боби Бадаревски, „Кон Lorraine Code, Ecological Thinking: The Politics of Epistemic Location“, Идентитети: списание за политика, род и култура, т. 6, бр. 1 (зима 2007): 215-220. Citation (Albanian): Bobi Badarevski, „Për Lorraine Code, Ecological Thinking: The Politics of Epistemic Location“, përkthim nga Maqedonishtja Xhabir Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 1 (Winter 2007): 215-220.